Left non-recurrent inferior laryngeal nerve in a patient with right-sided aortic arch and aberrant left subclavian artery. Issue 2 (April 2021) - Furukawa, Tatsuya; Otsuki, Naoki; Tomotsu, Masahiro; Tatehara, Shun; Morita, Naruhiko; Kojima, Yasutaka; Teshima, Masanori; Shinomiya, Hirotaka; Nibu, Ken-ichi
Abstract: Non-recurrent inferior laryngeal nerve (NRILN) is rare but one of the important anatomical variations in thyroid and parathyroid surgery. Almost all cases were observed on the right side with aberrant right subclavian artery and left NRILN have been reported in only five cases so far. Here, we reported a 38 year-old Japanese male with left NRILN accompanying adenomatous goiter. He was referred to our hospital for the surgical treatment of left thyroid goiter. Preoperative computed tomography revealed right-sided aortic arch and aberrant left subclavian artery with no signs of complete situs inversus viscerum, suggesting possible left NRLN. Left hemithyroidectomy was performed using nerve monitoring system. Intraoperatively, left recurrent laryngeal nerve was not identified along tracheoesophageal groove, but directly originated from vagal nerve and was running horizontally to larynx. Mobility of vocal cords were not impaired and postoperative course was uneventful. During thyroid surgery for the patients with right-sided aortic arch, meticulous care should be taken using nerve monitoring system to avoid nerve injury.